Pronouns and clitics in early language - Larrañaga, María Pilar; Guijarro Fuentes, Pedro (Studies in generative grammar ;, 2012)
Traditional grammars have stated that clitics are subject or object pronouns whose distributional features make them different from personal pronouns. This book focuses on the acquisition of personal and demonstrative pronouns as well as clitics with respect to determinative phrases in a variety of languages of the Romance family and several Indigenous languages, such as Quechua. A particularly original aspect of the present volume is that it not only addresses syntactic issues, but also semantic and pragmatic questions that have been widely neglected in the literature. It also reports on acquisition data of languages, such as Quechua, which have not attracted the attention of researchers until very recently.